The smart growth manual - Duany, Andres; Speck, Jeff.;Lydon, Mike. (New York : McGraw Hill Education, 2010)
Everyone is calling for smart growth...but what exactly is it? In The Smart Growth Manual, two leading city planners provide a thorough answer. From the expanse of the metropolis to the detail of the window box, they address the pressing challenges of urban development with easy-to-follow advice and broad array of best practices. With their landmark book Suburban Nation, Andres Duany and Jeff Speck "set forth more clearly than anyone has done in our time the elements of good town planning" (The New Yorker). With this long-awaited companion volume, the authors have organized the latest contributions of new urbanism, green design, and healthy communities into a comprehensive handbook, fully illustrated with the built work of the nation's leading practitioners.
1. Regional principles -- 2. The regional plan -- 3. Regional transportation -- 4. Natural context -- 5. Neighborhood components -- 6. Neighborhood structure -- 7. Thoroughfare network -- 8. Thoroughfare design -- 9. Public streetscape -- 10. Private streetscape -- 11. Parking -- 12. Building types -- 13. Green construction -- 14Architectural design -- Appendix: Useful statements -- Smart growth directory -- Acknowledgments -- Image credits -- Index.
Includes index.
Keywords: CITIES AND TOWNS